Marketing - Baines, Paul, 1973-; Fill, Chris (Oxford : Oxford University Press, 2014)
Linked to an online resource centre and instructor's DVD, this textbook introduces the basic principles of marketing. It includes numerous contemporary case studies, chapter summaries and review questions.
Publication date from publisher's website.
Previous edition by Paul Baines, Chris Fill and Kelly Page, 2011.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Marketing -- Textbooks; Marketing -- Case studies; Marketing -- Management -- Textbooks; Marketing -- Management -- Case studies